Feasibility of Students English Textbook for Junior High School - Sakoikoi, Marlina; Syafar, Dian Noviani; Putri, Dian Mega (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2024)
This study aims to analyse the feasibility of the English student textbook "When English Rings A Bell" by Siti Wachidah for class VIII SMP. This study used a descriptive method in a qualitative approach. The data obtained in this study result from an assessment in the form of a frequency score. Data processing for the feasibility of the contents of the book uses an assessment based on the BSNP. The researcher used the student’s English textbook "When English Rings A Bell" as a data source to find research results, and the researcher focused on the suitability of the material with core competencies (KI) and basic competencies (KD). The results of the study showed that the suitability of the material with core competencies (KI) and basic competencies (KD) scores 90.30% or the good category for the feasibility standards for English textbooks. From this percentage, it can be found that the score for the appropriateness of the contents of the English textbook and how the suitability of the material with the core competencies (KI) and basic competencies (KD) is 90.80% or the good category.